PERANCANGAN INSTALASI LISTRIK PADA GEDUNG MARKAS KOMANDO DIREKTORAT KEPOLISIAN PERAIRAN DAN UDARA KEPOLISIAN DAERAH SULAWESI TENGAH DI DESA WANI - Mohammad Agrimansyah; Nurhani Amin; Muhammad Sarjan (Foristek, 2020)
In office buildings, electrical energy is needed to meet the needs of lighting to electronic equipment used in the building. To support all of that, a reliable electrical installation system is needed so that all office activities can run well without causing significant problems. Therefore the planning of the electrical installation system in a building must refer to the applicable rules and regulations in accordance with PUIL and SNI. The design carried out refers to PUIL 2011, SNI 03-6575-2001 (Lighting System Design Procedures). The entire electrical installation system gets a 3 Phase supply from PLN. The total power in this building is 80000 watts, so the power needed from PLN to connect is 160 KVA. Conductors used in this installation, use cables with NYM and NYY types with varying sizes in accordance with the calculation of the conveying CRC that has been done.